Confirmatory Factor Analyses of Adolescent Education Character by Families/Parents In Premarital Sexual Prevention In Jember, Indonesia - Iis Rahmawati; Dewi Suminar Retno; Oedojo Soedirham; Pingky Saptandari (NurseLine Journal, 2018)
Adolescents are often involved in various risks of sexual behavior that are detrimental to health, social, and economic consequences, therefore parents are the first and foremost educators for children and have an important role in providing children’s character education to avoid premarital sexual behavior. The research sample was 229 students in six high schools in Jember Regency. The study used multistage random sampling technique. Variables in adolescent character education include indicators of teaching, motivating, habituation, modeling and enforcement of rules. Data analysis uses confirmatory factor analyze (CFA) with data estimation parameters using software (analysis of moment structures (AMOS) version 21). P-value of character education for adolescents by family/parents to teaching (0.000), p-value of adolescent character education by family/parents to motivation (0.000), p-value of character education for adolescents by family/parents to study (0,080), the value of character education for adolescents by family/parents to habituation (0.000), the value of adolescent character education by family/parents to enforcement of the rules (0.000). The model fit value in the comparative fit index (CFI) (0.897). Adolescent character education can be formed through teaching, motivating, imitating, habituating and enforcing the rules of parents to teenagers.